Does the Statutory Overtime Premium Discourage Long Workweeks? - Stephen J. Trejo (Institute for the Study of Labor (IZA), 2001)
Using a pooled data set consisting of 20 annual observations on each of eleven major industry groups, I estimate the effects of overtime pay regulation on weekly work schedules. After controlling for workweek trends within industries, the sharp expansions in overtime pay coverage resulting from legislative amendments and Supreme Court decisions produced no discernible impact on overtime hours. This finding is consistent with a model of labor market equilibrium in which straight-time hourly wages adjust to neutralize the statutory overtime premium.
Keywords: J33; J38; J23; 330; Overtime; work hours; compensating differential; Überstunden; Lohn; Arbeitsrecht; Arbeitszeit; Ökonomischer Anreiz; Schätzung; USA